XPO1-inhibitor Selinexor induces MGMT expression by activating PKA-CREB signaling in IDH wildtype glioblastoma - Mapunda, Josephine A.; Suzuki, Yuta; Burgenske, Danielle; Decker, Paul A.; Zhang, Lin; Eckel-Passow, Jeanette E.; Sarkaria, Jann N.; Kitange, Gaspar J. (Frontiers in Oncology, 2025)
PurposeThe temozolomide (TMZ) resistance mechanisms in MGMT-promoter methylated IDH wildtype glioblastoma (GBM) tumors are poorly known. This study aimed to identify potential modulators of TMZ resistance in methylated GBM cells.MethodsA genome-wide shRNA library screen was conducted to identify genes modulating resistance in a TMZ-resistant model of MGMT-methylated U251 GBM cells. The Incucyte Device was used for live cell growth monitoring, and DNA damage was assessed by foci staining.ResultsExportin (XPO1) was among the identified candidate TMZ-resistant genes, and the XPO1 inhibitor Selinexor was selected for further investigations. The MGMT-unmethylated GBM6 cells were sensitive to Selinexor alone, without additional sensitization when combined with TMZ. In contrast, MGMT-methylated GBM22 cells were relatively sensitive to Selinexor alone and were significantly sensitized to the Selinexor/TMZ combination. Interestingly, silencing MGMT sensitized GBM6 cells to the combined Selinexor/TMZ treatment, while forced exogenous MGMT expression blocked the sensitivity of U251 cells to the combined Selinexor/TMZ treatment. Selinexor treatment induced MGMT expression concurrently with increased phosphorylation of serine 133 of CREB protein (pCREBS133) in GBM6 and other MGMT-promoter unmethylated GBM cells. Finally, Selinexor-induced MGMT expression and pCREBS133 were blocked by the protein kinase A inhibitor H89, suggesting a role for PKA-CREB signaling in this process.ConclusionsThis study demonstrates XPO1 as a mediator TMZ resistance in MGMT-methylated GBM cells, and that MGMT expression status is a potential determinant of sensitivity to Selinexor/TMZ treatment in GBM cells. These findings also uncover a novel mechanism linking Selinexor with PKA-CREB-mediated MGMT expression, suggesting that Selinexor may enhance MGMT-dependent TMZ resistance in GBM.